Cerebrospinal fluid‐specific oligoclonal bands in dogs with idiopathic epilepsy - Junwei Föhr; Julia K. Prümmer; Arianna Maiolini; Eliane Marti; Ilijas Jelcic; Beatriz Vidondo; Mario Ziegler; Andrea Bathen‐Nöthen; Andrea Tipold; Holger A. Volk; Veronika M. Stein (Journal of Veterinary Internal Medicine)
Abstract Background In dogs with idiopathic epilepsy (IE), 33% develop resistance to conventional anti‐seizure medication (ASM) despite adequate treatment. In human medicine, an immune‐mediated etiology is suspected in a subset of ASM‐resistant patients with epilepsy and cerebrospinal fluid (CSF)‐specific immunoglobulin G (IgG)‐type oligoclonal bands (OCBs) have been detected. In dogs, cases of autoimmune encephalitis recently were reported. Neuroinflammation may provide an additional explanation for the lack of response of certain dogs with IE to ASM. Hypothesis Cerebrospinal fluid‐specific OCBs are found in a subgroup of dogs with ASM‐resistant IE. Animals Eighty‐four dogs with IE were recruited from 3 referral centers and classified based on their response to ASM treatment (responsive, n = 56; resistant, n = 28). Methods Detection of OCBs was performed using isoelectric focusing (IEF) followed by immunoblotting. Associations of CSF‐specific OCBs with seizure type, severity, and response to ASM were calculated using logistic regression models. Results The overall frequency of CSF‐specific OCBs in dogs with IE was 15.5% (95% confidence interval [CI], 8.5%‐25%). In dogs with ASM‐resistant IE, 21.4% (6/28) had CSF‐specific OCBs compared with only 12.5% (7/56) in those responsive to ASM, but no evidence of an association was detected (odds ratio, 1.9; 95% CI, 0.57‐6.35; P = .29). Conclusions and Clinical Importance Cerebrospinal fluid‐specific OCBs were detected in a subgroup of dogs with IE. This finding could indicate that intrathecal IgG synthesis as a sign of neuroinflammation may play a role in disease pathogenesis.